Experimental Verification of a Battery Energy Storage System for Integration with Photovoltaic Generators - Singh, R.; Taghizadeh, S.; Tan, N.M.L.; Mekhilef, Saad (Hindawi Publishing Corporation, 2017)
This paper presents the experimental verification of a 2 kW battery energy storage system (BESS). The BESS comprises a full-bridge bidirectional isolated dc-dc converter and a PWM converter that is intended for integration with a photovoltaic (PV) generator, resulting in leveling of the intermittent output power from the PV generator at the utility side. A phase-shift controller is also employed to manage the charging and discharging operations of the BESS based on PV output power and battery voltage. Moreover, a current controller that uses the - synchronous reference frame is proposed to regulate the dc voltage at the high-voltage side (HVS) to ensure that the voltage ratio of the HVS with low-voltage side (LVS) is equivalent to the transformer turns ratio. The proposed controllers allow fast response to changes in real power requirements and results in unity power factor current injection at the utility side. In addition, the efficient active power injection is achieved as the switching losses are minimized. The peak efficiency of the bidirectional isolated dc-dc converter is measured up to 95.4% during battery charging and 95.1% for battery discharging.